A comparison of fresh and used aircraft oil for the identification of toxic substances linked to aerotoxic syndrome. (September 2016) - Megson, David; Ortiz, Xavier; Jobst, Karl J.; Reiner, Eric J.; Mulder, Michel F.A.; Balouet, Jean-Christophe
Abstract: Fresh and used aircraft engine lubricants (Mobil Jet Oil II) were analysed using a Fourier Transform Ion Cyclotron Resonance Mass Spectrometer (FTICRMS) and comprehensive two dimensional gas chromatography with high resolution time of flight mass spectrometry (GCxGC-HRTOFMS). The composition of the fresh oil was established, with special focus to its tricresyl phosphate (TCP) content as this has formed the focus for most investigations into aerotoxic syndrome. The results showed that only four TCP isomers were present at detectable levels in the fresh oil: mmm-TCP, mmp-TCP, ppm-TCP and ppp-TCP. The results indicate that the formulation of Mobile Jet Oil II does not contain the more toxic ortho substituted TCP isomers at concentrations above 0.0005%. The temperatures of jet engines during operation are greater than 200 °C which creates the potential to alter the composition of the original oil and create other toxic compounds. The results show there may be a significant risk from alkylated cresyl phosphates, which were identified in the used oils at concentrations calculated in the range of 0.13–0.69%. w/w. Several xylenyl and ethylphenyl phosphates have been shown to exhibit a similar toxicity to ortho substituted TCP isomers which makes there discovery in used oil significant. These compounds should be included in future aircraft air quality studies and when assessing the risks and causes of aerotoxic syndrome. Highlights: High resolution mass spectrometry was used to identify toxic compounds in jet oil. Ortho substituted TCP was not detected in jet oil. Alkylated TCP was detected in used jet oil at 0.13–0.69%. w/w. Previous air quality studies may have underestimated the risks from OPs.